Dynamic Remodeling of the Plastid Envelope Membranes – A Tool for Chloroplast Envelope in vivo Localizations - Breuers, Frederique K.; Braeutigam, Andrea; Geimer, Stefan; Welzel, Ulla Y.; Stefano, Giovanni; Renna, Luciana; Brandizzi, Federica; Weber, Andreas P. (Frontiers in Plant Science, 2012)
Two envelope membranes delimit plastids, the defining organelles of plant cells. The inner and outer envelope membranes are unique in their protein and lipid composition. Several studies have attempted to establish the proteome of these two membranes; however, differentiating between them is difficult due to their close proximity. Here, we describe a novel approach to distinguish the localization of proteins between the two membranes using a straightforward approach based on live cell imaging coupled with transient expression. We base our approach on analyses of the distribution of GFP-fusions, which were aimed to verify outer-envelope-membrane proteomics data. To distinguish between outer envelope and inner envelope protein localization, we used AtTOC64-GFP and AtTIC40-GFP, as respective controls. During our analyses, we observed membrane proliferations and loss of chloroplast shape in conditions of protein overexpression. The morphology of the proliferations varied in correlation with the suborganellar distribution of the overexpressed proteins. In particular, while layers of membranes built up in the inner envelope membrane, the outer envelope formed long extensions into the cytosol. Using electron microscopy, we showed that these extensions were stromules, a dynamic feature of plastids. Since the behavior of the membranes is different and is related to the protein localization, we propose that in vivo studies based on the analysis of morphological differences of the membranes can be used to distinguish between inner and outer envelope localizations of proteins. To demonstrate the applicability of this approach, we demonstrated the localization of AtLACS9 to the outer envelope membrane. We also discuss protein impact on membrane behavior and regulation of protein insertion into membranes, and provide new hypotheses on the formation of stromules.